Activation of nylon by alkaline glutaraldehyde solution for enzyme immobilisation - Salleh, Abu Bakar (Springer Science and Business Media LLC, 1982)
Nylon tube was directly activated by alkaline glutaraldehyde solution. PEI was utilised as a spacer molecule. Glucose oxidase was immobilised to the nylon tube after reactivating the spacer molecules with glutaraldehyde. On immobilising glucose oxidase there was more protein binding and higher immobilised enzyme activity when compared to immobilised enzyme tube activated by triethyloxonium salt. The optimal condition for direct glutaraldehyde activation of nylon was incubation with 18.5% (w/v) glutaraldehyde in 0.12M borate pH 9.0 for 15 min at 90 °.